Splenic abscess caused by Toxocara spp. in a lung transplant recipient, Marseille, France. Issue 4 (2nd June 2021) - Balacheff, Quentin; Lovato, Jean‐Baptiste; Coiffard, Benjamin; L'Ollivier, Coralie; Cassir, Nadim; Reynaud‐Gaubert, Martine
Abstract: Infections represent one of the leading causes of morbidity and mortality in solid organ transplantation (SOT) recipients. Although Toxocara species are prevalent worldwide, toxocariasis is an important neglected human disease that can manifest as visceral or ocular larva migrans, or covert toxocariasis. Herein, we report and discuss the first documented case of a splenic abscess associated with toxocariasis in a 69‐year‐old lung transplant recipient, in France. This case emphasizes the need to include prevention of toxocariasis in the management of lung transplant patients.